COVID-19 and misinformation: evaluating public awareness and the role of Aesthetic Medicine - D'Angelo, Marta; Solla, Daniele; Giaquinta, Samuele; Gambolò, Luca (Aesthetic Medicine, 2025)
Purpose: The COVID-19 pandemic underscored global vulnerabilities in handling such a widespread health crisis, significantly affecting the healthcare system. A relevant amount of misinformation from the general population was observed, which caused a loss of trust in the healthcare system. Misinformation could be reduced by medical consultation and aesthetic physicians could take part in this, playing an important role. Methos: This study assesses the general population's ability to differentiate between accurate and misleading COVID-19 information, which is a critical factor in managing public health responses and mitigating the spread of misinformation. A cross-sectional survey was conducted with 230 participants. Results: Results indicated a high level of understanding, with an average correct response rate of approximately 76%. No significant gender differences were found in survey scores. Interestingly, the younger age group (18-22 years) outperformed the 23-39 age group, despite the latter's higher education levels. Notably, 60% of respondents incorrectly believed that COVID-19-positive mothers should be separated from their children, contradicting health guidelines promoting mother-infant proximity for emotional and developmental benefits. Additionally, 40.5% misunderstood vaccination recommendations for immunodeficient individuals, and only 13% correctly understood proper hand sanitizer use, highlighting gaps in public health education. Conclusions: This study highlights some discrepancies regarding relevant information in the general population, emphasizing the essential role of medical counseling in combating misinformation. Aesthetic physicians should integrate comprehensive health education into patient interactions. The holistic approach, led by the aesthetic physician, could address misconceptions, and promote accurate health practices, such as proper hygiene, vaccination and health advice, thereby enhancing public health resilience against current and future pandemics. In an era where misinformation is rampant, effective counseling can significantly mitigate its impact, fostering a well-informed public capable of making sound health decisions.